FAKTOR PENDUKUNG DAN PENGHAMBAT KEBIJAKAN JANGKA PANJANG PEMERINTAH KABUPATEN KEDIRI DALAM PEMBANGUNAN CENTRAL BUSINESS DISTRICT - Haryanto Haryanto (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
The Government of Kediri Regency formed the icon of Kediri Regency by building Simpang Lima Gumul and Monuments. Thus, it is expected that there will be investments in the Simpang Lima Gumul area because it is a strategic road and location. This study was analyzed using the theory of the role of government and public policy. The research method in this journal uses descriptive qualitative methods. CBD is held in a multi-year and continuous system, meaning that the budget is carried out annually. The project is from exemption until completion from 2002-2012. The project phase includes land acquisition in 2002-2009, construction of monuments, construction of highways, and the fourth phase of construction of public facilities such as terminals, regional banks, the monument market on Sundays and the immigration office. While the construction of the new Hall was completed in 2012. This is still needed by investors for CBD development because of limited funding from the government. Supporting factors in the CBD development policy are cooperation with German, French and other networks. Inhibiting Factors of CBD formation, namely trade and industry locations that have not yet been established, there are still few business units built in the Simpang Lima Gumul area.